Pengaruh Harga Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Tigaras Café Di Jakarta Selatan - Yulinar Wahyuni; Triyadi Triyadi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract - This study aims to determine the Effect of Price and Service Quality on Customer Satisfaction at Tigaras Cafe in South Jakarta. The research methodology used is the Associative method. The population in this study were buyers at Tigaras Cafe, South Jakarta, with a sample size of 98 respondents. The data analysis methods used were simple linear regression, multiple linear regression, correlation coefficient, coefficient of determination, partial t-test, and simultaneous F-test. The results of the study indicate that: There is an effect of price on customer satisfaction at Tigaras Cafe, South Jakarta, where the calculated t value> t table (6.509> 1.985) and sig <0.05 (0.000 <0.05). There is an effect of service quality on customer satisfaction at Tigaras Cafe, South Jakarta, where the calculated t value> t table (4.457> 1.985) and sig <0.05 (0.000 <0.05). There is a simultaneous influence between price and service quality on customer satisfaction at Café Tigaras, South Jakarta, with a calculated f-value > f-table (21.873 > 3.092) and a sig value < 0.05 (0.000 < 0.05).